Rhizocompartments drive the structure of root-associated fungal communities in halophytes with different life forms - Mo, Zhengxian; Wang, Hengfang; Sun, Li; Zhang, Yabei; Wei, Shengtao; Huang, Hao (Frontiers in Plant Science, 2025)
IntroductionSymbiotic fungi with plants are important for plant nutrient uptake and resource redistribution.MethodsHigh-throughput sequencing was used to investigate the composition and driving factors of fungal communities in three rhizocompartments (root endosphere, rhizosphere soil, and non-rhizosphere soil) of different halophyte life forms in the National Nature Reserve of Ebinur Lake Wetland in Xinjiang, China.Results(1) The α-diversity index differed significantly among the three rhizocompartments of halophytes with different life forms (P < 0.05), and α and β-diversity were mainly driven by rhizocompartments. (2) Ascomycota and Basidiomycota were the dominant communities across various rhizocompartments in the different life forms. Aporospora and Monosporascus were the dominant fungal genera in the root endosphere of all three plant life forms. Alternaria was dominant in both rhizosphere and non-rhizosphere soils in herb. Penicillium and Knufia were the dominant in the rhizosphere and non-rhizosphere soils in shrub, respectively. While Penicillium and Aspergillus were dominant in both rhizosphere and non-rhizosphere soils in abor. (3) The complexity of the fungal co-occurrence network varied among plant life forms; the highest complexity was found in the rhizosphere soil of herb (11.102), the root endosphere of shrub (23.837) and in the non-rhizosphere soil of arbor (9.920). Furthermore, the co-occurrence networks of the three plant life forms in the three rhizocompartments were mainly positively correlated (86.73%–97.98%). (4) Root-associated fungal communities were significantly and strongly correlated with soil and root water content, soil and root total nitrogen, root and leaf total phosphorus, alkaline phosphatase, nitrate nitrogen and salt content in herb. While in shrub, root-associated fungal communities were strongly correlated with soil water content, available phosphorus, catalase and total phosphorus. However, arbor exhibited no significant correlations with soil and plant physicochemical factors.DiscussionThese results provide a theoretical foundation for understanding the complex interaction mechanism between desert halophytes and fungi and are of great significance for strengthening desert vegetation management and vegetation restoration in arid areas.